First report of in-situ preservation of a subcapsular parathyroid gland through super-meticulous capsular dissection during robotic radical thyroidectomy. (March 2019) - Qi, Xiaowei; Du, Junze; Liu, Haoxi; Cui, Xiang; Li, Yanling; Fu, Wenying; Jiang, Jun; Fan, Linjun
Abstract: Purpose: Meticulous capsular dissection can preserve the function of the parathyroid gland in most patients, but it is difficult to identify and preserve the subcapsular parathyroid gland. We performed in-situ preservation of the subcapsular parathyroid gland during robotic radical thyroidectomy using super-meticulous capsular dissection, and evaluated its effect on postoperative parathyroid function. Methods: A 45-year-old woman was admitted with bilateral thyroid nodules. Color Doppler ultrasound demonstrated a 7 × 7 × 6 mm hypoechoic area in the middle and inferior part of the right lobe and 3 × 3 × 3 mm hypoechoic nodule in the middle part of the left lobe. She was diagnosed with right thyroid papillary cancer by fine-needle aspiration. Robotic bilateral thyroidectomy plus right central lymph node dissection was performed. During the left thyroidectomy, we found that the left inferior parathyroid gland was just under the true capsule. Subsequently, the super-meticulous capsular dissection was performed for in-situ preservation of the parathyroid gland. Results: The patient's serum parathyroid hormone concentration was 43.77 pg/ml before and 37.98 pg/ml after surgery (normal: 15–65 pg/ml). Her blood calcium level was 2.21 mmol/l before and 2.18 mol/l after surgery (normal: 2.10–2.65 mmol/l). Conclusions: The super-meticulous capsular dissection, which could cut through the true capsule to identify subcapsular parathyroid and protect its anatomic structure as well as blood supply, is recommend for in-situ preservation of subcapsular parathyroid gland during robotic radical thyroidectomy. Highlights: The true capsule is carefully cut through to identify the subcapsular parathyroid. The anatomic structure of the subcapsular parathyroid gland is well preserved. The blood supply of the parathyroid gland is well protected by preserving the true thyroid capsule surrounding it.